VISUALIZATION OF DATA PROCESSING PROCESSES FOR THE INFORMATION SYSTEM OF INTELLECTUAL PROPERTY RIGHTS OBJECT COMMERCIALIZATION - SHILINH, Anna (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The aim of this article is to visualize the data processing processes for the information system of intellectual property rights commercialization. The article analyses the main legislative and regulatory documents governing the process of intellectual property rights commercialization in the information products and services market in Ukraine. It is also determined that the functioning of this information system will be influenced by external market factors. In particular, the main ones include economic development of the countries where the process of intellectual property rights commercialization takes place, legislation and regulatory framework of the country, financial regulation of the process of intellectual property rights commercialization. Based on these results, the author developed the structure of the data flow diagram of the information system for drafting an intellectual property sale and purchase agreement, taking into account external factors of influence. This data flow diagram includes such processes as determining the terms of the intellectual property contract for an intellectual property object, forming the relevant contract and confirming it. The paper also contains the structure of the data flow diagram for the transfer of product ownership and the intellectual property deposit and payment agreement, taking into account external factors of influence. It includes a description of such processes as the formation of a deposit agreement, order fulfilment control, and payment for the execution of the process of buying and selling an intellectual property object. The proposed visualization of data processing processes for the information system for commercialization of intellectual property rights objects includes a database of laws and regulations of Ukraine and can be expanded for use outside Ukraine. The results of the study are applied and can be used to development an appropriate information system of intellectual property rights commercialization, taking into account the influence of external factors of the market of information products and services.
Keywords: intellectual property; data flow diagram; information system; market of information products and services; commercialization